(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
International law constitutes a foundational element of contemporary international relations, providing legal norms and institutional mechanisms that regulate interactions among states and other international actors. In the context of globalization, increasing interdependence, and complex transnational challenges, international law plays a vital role in maintaining international order, promoting cooperation, and addressing global problems such as armed conflict, human rights violations, environmental degradation, and economic inequality. This article analyzes the role of international law through the IMRAD framework. Using a qualitative analytical approach, the study examines theoretical perspectives, legal instruments, and institutional practices. The results demonstrate that international law significantly influences state behavior by shaping norms, facilitating cooperation, and offering mechanisms for dispute resolution, despite persistent challenges related to enforcement and power asymmetry. The discussion highlights the continued relevance of international law as a core component of global governance in the contemporary international system.